“In English my name means hope. In Spanish it means too many letters”: Identity and Otherness in Sandra Cisneros’ Writings - Lemos, Márcia (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
Born into a Mexican family, American writer Sandra Cisneros has repeatedly given voice to characters marginalized not only for being female but also for being Chicanas. Though apparently simple in their narrative modes, Cisneros’ texts present the readers with many complex layers of meaning in their endeavour to represent female expectations, anxieties and concerns in a world that is still very much challenging for women. One core concern is certainly language, reflecting the author’s divide between Spanish, her family’s mother tongue, and English, her own native language, and the language in which she writes. This paper will focus on two works by Cisneros: her 1984 novel The House on Mango Street and her 2021 dual-language text Martita, I Remember You / Martita, te recuerdo: A Story in English and Spanish. The purpose of this paper is to address the importance of linguistic choices in representing female identities and experiences of otherness in a largely patriarchal society. The title is inspired by a passage in The House on Mango Street in which Esperanza, the young protagonist and narrator of the novel, reveals some discomfort about her own name and specially the way it is constantly mispronounced by English speakers, including her teachers at school. Echoing Virginia Woolf, in Cisneros’ coming-of-age 1984 novel, female identity is dependent not only on getting a house of her own (away from the barrio), but also her own name, one that could be “la simple carte photographique d’identité”, as Proust would put it in À la Recherche du Temps Perdu (754).